What worsens swallowing in esophageal achalasia? Insights from patient-reported outcomes - Cesarini, Alessandra; Scalese, Giulia; Mocci, Chiara; D’Alba, Lucia; Severi, Carola; Badiali, Danilo; Ribichini, Emanuela (Frontiers in Nutrition, 2026)
Introduction and aimsEsophageal achalasia (EA) is a rare motility disorder. Symptoms often impair quality of life (QoL) and lead to restrictive, self-managed diets with potential nutritional deficiencies. The study aimed to assess dietary patterns and nutritional status in EA patients.Materials and methodsEA patients, retrospectively recruited from January 2018 to August 2024, filled out a 15-day diary to record ingested food and relative symptoms onset for each meal. Estimated caloric intake and macronutrient composition were compared to those recommended by the Italian Society of Human Nutrition (SINU). EA activity was assessed with Eckardt Symptoms Score (ESS) and QoL with the MD Anderson Dysphagia Inventory (MDADI).ResultsOf 44 patients (24M, 20F; 56.9 ± 15.7 years), 79% had active disease (ESS ≥3). The mean daily caloric intake was 1,573 ± 368 kcal/die, significantly lower than the estimated needs (p < 0.0001). Macronutrients distribution was unbalanced with an increase in fats (37.8%), a decrease in carbohydrates (43.2%), and insufficient fiber intake (14 g). The most common symptom-triggering foods were bread, pasta, pizza (50–60%). Additionally, 60% reported worsened symptoms with cold foods, while 53% found relief with hot foods.ConclusionThis study highlights the pivotal role of dietary factors, particularly food consistency and temperature, in the management of EA, supporting the incorporation of individualized dietary counseling into standard EA care.